2004
DOI: 10.1111/j.0887-378x.2004.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Driven to Tiers: Socioeconomic and Racial Disparities in the Quality of Nursing Home Care

Abstract: Nursing home care is currently a two-tiered system. The lower tier consists of facilities housing mainly Medicaid residents and, as a result, has very limited resources. The nearly 15 percent of U.S. nonhospital-based nursing homes that serve predominantly Medicaid residents have fewer nurses, lower occupancy rates, and more health-related deficiencies. They are more likely to be terminated from the Medicaid/Medicare program, are disproportionately located in the poorest counties, and are more likely to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
489
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 414 publications
(516 citation statements)
references
References 68 publications
(87 reference statements)
25
489
2
Order By: Relevance
“…4 A tiered system of nursing home care that concentrates blacks in marginal-quality nursing homes also appears to exist. 5 n Historical background. Historically, segregation and discrimination in access to higher-quality nursing homes in the United States have never been systematically addressed.…”
mentioning
confidence: 99%
“…4 A tiered system of nursing home care that concentrates blacks in marginal-quality nursing homes also appears to exist. 5 n Historical background. Historically, segregation and discrimination in access to higher-quality nursing homes in the United States have never been systematically addressed.…”
mentioning
confidence: 99%
“…Facilities with higher percentages of Medicaid residents have been found to be associated with more deficiencies [38][39], higher odds of hospitalization [40][41], more complaints [42], higher likelihood of voluntary or involuntary terminations [39,43], higher rates of antipsychotic medication prescription [39,44], and higher rates of physical restraint use and pressure ulcers [39]. Nursing homes with higher proportions of black residents and rural nursing homes also exhibited worse processes and outcomes [45][46][47].…”
Section: Evidence Of Low Quality In Nursing Homes and Changes In Qualmentioning
confidence: 99%
“…The level of resources available has substantial influence on quality of care. Studies have found that nursing homes with high concentrations of Medicaid patients were more like to have quality of care problems due to very limited resources compared to nursing homes with low concentrations of Medicaid patients [39,[188][189]. In addition, public reporting may increase the divide between providers that are more or less able to improve quality [190].…”
Section: Differential Effects Of Medicaid Reimbursement Change On Quamentioning
confidence: 99%
See 1 more Smart Citation
“…Race as recorded in the Medicare denominator file was aggregated into three categories (white, black, and other) because ,1% of the parent study's cohort had race besides white or black (1). We also included number of hospitalizations within 90 days before SNF admission, comorbid conditions and Charlson comorbidity score based on International Classification of Diseases-Ninth Revision (ICD-9) codes in inpatient Medicare claims (19) From NH Compare, we obtained information on the following SNF characteristics: facility bed count, ownership status (unknown, for-profit, government, or nonprofit), registered nurse hours per resident day, and licensed practical nurse hours per resident day (20).…”
Section: Variablesmentioning
confidence: 99%